Hexavalent chromium induced metabolic reprogramming, carcinogenesis and tumor progression through PDK1 upregulation - Liu, Wen-Jing; Wang, Lin; Sun, Fan-Li; Zhou, Feng-Mei; Zhang, Rui-Ke; Liu, Jie; Zhao, Min; Wang, Li-Hong; Qin, Yan-Ru; Zhao, Yan-Qiu; Qiu, Jian-Ge; Jiang, Bing-Hua (Ecotoxicology and environmental safety, 2024)
Lung cancer is the leading factor of cancer-related death in the worldwide. Hexavalent chromium [Cr(VI)] is a potential carcinogen for inducing lung cancers. To understand new mechanism of Cr(VI)-induced tumorigenesis and cancer development, we identified that PDK1 expression levels were greatly increased in chromium-transformed cells (Cr-T) compared to the parental BEAS-2B (B2B) cells by proteomic profiling and Western blotting; PDK1 levels were also induced in lung cancer cell lines and in lung samples of mice exposed to Cr(VI). Cr(VI) increased Warburg effect, cell migration, proliferation and colony formation through PDK1 upregulation. To identify the mechanism of PDK1 induction, we performed miRNA-seq analysis of Cr-T and B2B cells, and found miR-493 levels was significantly suppressed by Cr(VI). PDK1 was induced by miR-493 suppression, and was a direct target of miR-493. Interestingly, we also found HIF-1α was directly targeting by miR-493 and was induced by miR-493 downregulation. HIF-1α expression levels were upregulated in lung samples of mice with Cr(VI)-exposure. PDK1 was induced by HIF-1α, showing miR-493 suppression can directly induce PDK1 as well as through HIF-1α induction. MiR-493 overexpression was sufficient to suppress tumor growth, PDK1 and HIF-1α expression in vivo. We also showed that levels of miR-493 suppression, HIF-1α and PDK1 elevations were strongly correlated with poor prognosis of lung cancer subjects. These results demonstrate both HIF-1α and PDK1 expression are induced by Cr(VI)-mediated miR-493 suppression, and MiR-493/HIF-1α/PDK1 axis is a new pathway in Cr(VI)-inducing carcinogenesis and tumor growth. [Display omitted] •PDK1was upregulated and important in Cr(VI)-induced cell transformation and carcinogenesis.•MiR-493 was decreased in Cr-T cells, miR-493 overexpression was sufficient to suppress Cr(VI)-induced carcinogenesis.•PDK1 and HIF-1α were direct targets of miR-493.•MiR-493/HIF-1α/PDK1 axis regulated Cr(VI)-induced tumor growth and angiogenesis.